A biological and biochemical study of two species of sea bream Acanthopagrus arabicus (Iwatsuki, 2013) and Sparidentex hasta (Valenciennes, 1830) fromShatt Al-Arab River – Southern Iraq - Yaseen, Ali taha; Alkareem Taher Yesser , Qusay Hamid Al-HamadanyAbd (International Journal of Psychosocial Rehabilitation, 2020)
Due to the importance of sea bream, Acanthopagrus arabicus (Iwatsuki, 2013) and Sparidentex hasta (Valenciennes, 1830),the current study aimed to identify some of the biology aspects and biochemical contents of these two species for both fisheries and aquaculture industry.During the time from January 2018 to June 2018, samples of both species were obtained. In which the relationship between fish lengths and weights was studied, a simple regression between lengths and weights and their mathematical expression was analyzed.The absolute condition factor (K)and the relative condition factor (Kn) of both species were also determined.The study found that the sizes of S hasta fish are larger than that of the sizes of A arabicus, as their lengths ranged between 9 to 25 cm (average length of 17 cm) while they were in the A. arabicus fish 9-19 cm (average length of 14 cm).and the weights of S. hasta fish ranged between 19.64 g to 87.32 g, with an average weight of 52.24 g, whereas in the A. arabicus, it was 18.10 to 43.70 g, with average weight of 37.92 (g).The equation of the length-to-weight relationship for the A.rabicus fish was W= 1.541 + 2.639 L, and W= 0.39 + 2.800L for S. hastafish. The absolute (K) were 44311and 44013of the two species respectively, relative condition (Kn) were 04910 for A. arabicus and 04999 for S. hasta.Fish muscles were taken to measure the chemical composition. The results indicated that S.hasta fish have the highest percentage of meat (yield %), high protein and fat content, as the yield % reached 48.97 ± 2.54 %, protein content 19.5 ± 1.89, and fat content 8.1 ± 0.53 compared to yield % , protein and fat content of A.arabicusfish meat45.63±2.08%, 18.79 ± 0.50 and 3.31 ± 1.01%respectively. Based on these results, the two species are good source of protein, fat and minerals, and provide useful data for both fisheries management, and aquaculture industry.